Intention to Adopt Fintech among Grocery Buyers: A Moderation Analysis - Pokharel, Jhabindra; Khanal, Smriti (Journal of Emerging Management Studies, 2024)
Purpose – Fintech service is an emerging issue around the globe. This paper is intended to investigate the perception of grocery buyers regarding adoption of financial technology. Furthermore, this paper also aimed to analyze the moderating effect of gender on the intention to adopt Fintech among grocery buyers. Design/methodology/approach – The research design for the paper was descriptive, correlational, and causal-comparative. The convenience sampling technique was used to collect data and formulate the hypotheses for the analysis. The sample size for the research was 250 respondents, and the data were collected through a structured questionnaire. Findings – Quantitative outcomes from the analysis demonstrated a significant positive effect of perceived ease of use, perceived value, perceived usefulness, perceived enjoyment and trust, and security concern on the intention to adopt Fintech among grocery buyers. Furthermore, intentions of male and female significantly differed in perceived ease of use and trust, and security concern. However, this study could not find the gender moderating the effect on perceived value, perceived usefulness, and perceived enjoyment on intention to adopt Fintech among grocery buyers. Implications – The research emphasized on user-friendly interfaces, convenient use, enjoyable experiences, and reliable security. Grocery suppliers could highlight on customization and personalization, gamified shopping experiences, virtual store tours, and product demonstrations. Addressing gender disparities through customized marketing and inclusive support could strengthen Fintech use among female consumers. The research contributed to establishing theories like TAM. It paved the way for further research into the nuanced dynamics of technology adoption, user perceptions, and retail contexts, enriching the understanding of Fintech’s role in modern consumer behavior. Originality/value – The research aimed to investigate the moderating effect of gender on Fintech adoption among grocery buyers. The research also supported technology acceptance model (TAM). The research provides novel and valuable contribution to the evolving field of financial technology. This paper contributed into an area that has received limited attention, exploring how gender moderates consumer behavior in financial services and retail transactions.